The Effect of Lavender Essential Oil On Post-Caesarean Section at Sekayu District General Hospital in 2020 - Novita Anjelia (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Caesarean section labor causes discomfort in the area of the surgery scar. One of the condition that cause patient discomfort is pain. Pain management can be done with a combination of pharmacology and nonpharmacology farmakologi. One of the non-pharmacological therapy that are good in reducing post cesarean section pain is to use lavender essential oil. This study was conducted to determine the effect of lavender essential oil on post caesarean section pain in The Sekayu District General Hospital in 2020. This study used Pre-exeperimental designwih one group pretest postest approach, the sampling technique used purposive sampling, with a sample of 30 respondents. Before being given Lavender Essential Oil, here were 29 respondents (96,7%) who experienced moderate pain dan 1 respondent who experienced mild pain (3,3%) then after being given Lavender Essential Oil there was a reduction in the level of pain with 29 respondents at mild pain levels (96,7%) and 1 respondent at moderate pain levels (3,3%). Mc Nemar test result showed ρ value = 0,000 (ρ value < (0,05)), wich means that there is an effect of Lavender Essential Oil on post caesarean section at Sekayu District General Hospital in 2020. To overcome post caesareansection midwives are expected to provide easy and safe mehods, one of them by using Lavender Essential Oil